Penerimaan Mobile Banking di Kalangan Nasabah Perbankan Syariah - Muhammad Khaerul Muttaqien; Moh Khoirul Anam; Tajudin Mas’ud; Hamli Syaifullah (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to investigate the factors that determine the acceptance of mobile banking among Islamic bank customers by using the unified theory of acceptance and use of technology (UTAUT) model and two other additional variables, namely perceived risk and cost. By using SmartPLS 3.29, the empirical findings of this study show that performance expectations, business expectations, and facilitating conditions have a significant effect on the intention to use mobile banking. The empirical findings of this study also show that intention has a significant effect on the use of mobile banking. Meanwhile, perceived social influence, costs and risks do not have a significant effect on the intention to use mobile banking. Keywords: UTAUT, Risk, Cost, Mobile Banking, Islamic Bank,